A case–control study on the association between adherence to a Mediterranean-style diet and breast cancer - Sadeghi, Omid; Eshaghian, Niloofar; Benisi-Kohansal, Sanaz; Azadbakht, Leila; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2023)
Background: Previous studies on the diet-breast cancer relationship are mostly from western nations and data from Middle East countries are scarce, where the prevalence of breast cancer is estimated to be high; such that it ranks first among other cancers. This population-based case-control study aimed to investigate the association between adherence to a Mediterranean-style diet and breast cancer in Iranian women. Methods: We enrolled 350 pathologically confirmed new cases of breast cancer and 700 controls which were matched with cases in terms of age and socioeconomic status. Dietary intakes were assessed using a 106-item Willett-format semi-quantitative dish-based food frequency questionnaire (FFQ). Mediterranean diet score was calculated based on participants’ dietary intakes obtained from FFQ. Data on potential confounding variables were also collected using pre-tested questionnaires. Results: We found a significant inverse association between adherence to the Mediterranean diet and odds of breast cancer so that after controlling for potential confounders, individuals in the highest tertile of the Mediterranean diet score had 57% lower odds of breast cancer compared with those in the lowest tertile (OR: 0.43, 95% CI: 0.28-0.67). Such an inverse association was also observed for postmenopausal women; such that after taking potential confounders into account, high adherence to a Mediterranean diet was associated with 63% lower odds of breast cancer (OR: 0.37, 95% CI: 0.23-0.60). This association was not significant in premenopausal women. Conclusion: Our findings show that adherence to a Mediterranean-style diet is associated with reduced odds of breast cancer. Prospective studies are needed to further examine this association.